Development and clinical validation of a circulating tumor DNA test for the identification of clinically actionable mutations in nonsmall cell lung cancer. Issue 4 (30th January 2018) - Liu, Liping; Liu, Han; Shao, Di; Liu, Zu; Wang, Jingjing; Deng, Qiuhua; Tang, Hailing; Yang, Haihong; Zhang, Yalei; Qiu, Yuan; Cui, Fei; Tan, Meihua; et al.
Abstract: Molecular analysis of potentially actionable mutations has become routine practice in oncological pathology. However, testing a wide range of oncogenes and mutations can be technically challenging because of limitations associated with tumor biopsy. Circulating tumor DNA (ctDNA) is a potential tool for the noninvasive profiling of tumors. In this study, we developed a next‐generation sequencing (NGS)‐based test for the detection of clinically relevant mutations in ctDNA and evaluated the feasibility of using this ctDNA NGS‐based assay as an alternative to tissue genotyping. Tissue and matched blood samples were obtained from 72 patients with advanced nonsmall cell lung cancer (NSCLC). NGS‐based testing was performed using plasma cell‐free DNA (cfDNA) samples of all 72 patients as well as tumor DNA samples of 46 patients. Of the remaining 26 patients, tDNA was tested by amplification refractory mutation system PCR (ARMS‐PCR) because of insufficient tissue sample or quality for NGS. Of the 46 patients who had tDNA and cfDNA NGS performed, we found 20 patients were concordant between tDNA and ctDNA alterations and 21 sample pairs were discordant because of additional alterations found in tDNA. Considering all clinically relevant alterations, the concordance rate between tDNA and ctDNA alterations was 54.9% with a sensitivity of 53.2% and a specificity of 75.0%. Our findings demonstrate that targeted NGS using cfDNA is a feasible approach for rapid and accurate identification of actionable mutations in patients with advanced NSCLC, and may provide a safe and robust alternative approach to tissue biopsy.